Evaluasi Penyelenggaraan Kota Sehat Di Pemerintahan Daerah Kota Palopo Tahun 2022: Evaluation of the Implementation of Healthy Cities in the Regional Government of Palopo City in 2022 - Amaliya, Ceria; Rusyidi, Arni Rizqiani; Haeruddin, Haeruddin; Suharni, Suharni; Arman, Arman; Ahri, Reza Aril (Postgraduate Program in Public Health, Universitas Muslim Indonesia, 2023)
Background: Healthy City depicts a clean, comfortable, safe, and healthy city condition for residents to live in. The establishment is achieved through the implementation of several arrangements with integrated activities agreed by the community and local government (Firman et al., n.d.). The purpose of the study was to determine the evaluation of the implementation of a Healthy City in Palopo Regional Government in 2022. Methods: This study performed mixed research that researchers applied a combination of qualitative and quantitative approaches to be carried out together in this study so that the results obtained more comprehensive, valid, reliable, and objective data. In quantitative research, this study took place at Healthy City Forum based on the achievement such as indicators and arrangements for Healthy Cities. While, in a qualitative approach, it involved informants, including the Chair of the Healthy City Development Team in Palopo and the Head of SKPD at each research locus. Results. The results of the study based on the results of the achievement review of a healthy city arrangement in Palopo City consisted of the Settlement of Facilities and Infrastructure of 94.02% (Healthy), Order of Traffic Order Areas of 98% (Healthy), Industrial and Healthy Office Arrangements of 94.11% (Healthy). ), Healthy Tourism Order of 90.62% (Healthy), Food Security and Nutrition Order of 89.58% (Healthy), Healthy Independent Community Life Order of 96.05% (Healthy), and Healthy Social Life Order of 91 ,66% (Healthy). Conclusions and recommendations. The evaluation of the implementation of a Healthy City in Palopo government operates in accordance with the procedures that have been set and Healthy City Forum prepares for a Healthy City upcoming assessment in 2023. It is recommended that the government should act more actively in coordination, socialization, monitoring, and guidance in this healthy city program properly to create a clean, safe, comfortable, and healthy city that can improve facilities and productivity as well as the community economy in Palopo. Therefore, strong cooperation is required among the community, government, and the private sector in accordance with their respective roles and objectives in each healthy city program.